Diet and niche overlap of the pompano (Trachinotus carolinus) and palometa (Trachinotus goodei) (Perciformes, Carangidae) in a surf zone beach in southeastern Brazil - Junior, Teodoro Vaske [UNESP]; Viliod, Marcela Coffacci Lima [UNESP]; Knoeller, Jéssica Dos Santos Muniz (My University, 2018)
The diet and niche overlap of the pompanos Trachinotus carolinus and T.goodei in a surf zone were studied based on 352 specimens of T. carolinus and 53 of T. goodei ranging from 10 to 165 mm total length. The study was carried out in a sand beach in southeastern Brazil, where the fishes were captured with a seine net measuring 10 x 2 meters and 4.0 mm mesh. A total of 34 prey items were found for T. carolinus and 26 for T. goodei, represented mainly by Copepoda, Insecta, Decapoda larvae, Polychaeta, Mollusca, Echinodermata, and fishes. The diet showed a remarkable predominance of insects Formicidae and zooplankton represented mainly by copepods, Decapod larva, and Mysida among other prey groups. No differences were observed for day and night periods, stomach fullness, or prey length and predator length relationships. Both species share 72.16% of the prey items. The uncommon high presence of insects in the stomachs may be associated with the sample area near to coastal vegetation, and the presence of human wastes from urban zone.
Keywords: Carangidae; Diet; Prey-predator; Stomach content; Zooplankton